8+4(z-2)=-5z+5

Simple and best practice solution for 8+4(z-2)=-5z+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+4(z-2)=-5z+5 equation:


Simplifying
8 + 4(z + -2) = -5z + 5

Reorder the terms:
8 + 4(-2 + z) = -5z + 5
8 + (-2 * 4 + z * 4) = -5z + 5
8 + (-8 + 4z) = -5z + 5

Combine like terms: 8 + -8 = 0
0 + 4z = -5z + 5
4z = -5z + 5

Reorder the terms:
4z = 5 + -5z

Solving
4z = 5 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
4z + 5z = 5 + -5z + 5z

Combine like terms: 4z + 5z = 9z
9z = 5 + -5z + 5z

Combine like terms: -5z + 5z = 0
9z = 5 + 0
9z = 5

Divide each side by '9'.
z = 0.5555555556

Simplifying
z = 0.5555555556

See similar equations:

| X^2(X^2-16)-64(X^2-16)=0 | | (1/4^2)-(3/2)-(7/4) | | x(3+7)-5=5(x+4)+5 | | y=8/3*1+8 | | 3r^2-5r-2= | | 1/4^2-3/2-7/4 | | n/7+6=13 | | 4=3x-8-2(5-x) | | t^4+43t^2+42=0 | | r^2-3r+2= | | 3c-12=145c | | 3k^2+-14k+8= | | 3m^2-8m=0 | | -1.6(1+7.6r)=-90.368 | | -7/3=-7/2u-7/5 | | 3(-6+x)=4x-1/3 | | (3x+7/4)+(x+22/5)=9 | | -8*1+7y=-56 | | 5(3m+8)+8(m+4)=95 | | 9d^2+18d+8=0 | | 9a-3a=2a+24 | | 3x+7/4+x+22/5=9 | | (5x-9)(2x+3)= | | t-(9)=4 | | 2x-5+7x=11-3x+4 | | 5(3m+8)+8(m+4)=63 | | (5z/2z)*(9/z) | | nb=n+a | | ((-4z^6)/5z)*(9/z) | | 14=(-p-8) | | x+6=x-7 | | (w-3)/(w-6)=(w+5)/(w-3)+1 |

Equations solver categories